CSR, Trust, Brand Loyalty and Brand Equity: Empirical Evidences from Sportswear Industry in the NCR Region of India. Issue 1 (June 2019) - Sharma, Rajesh; Jain, Vranda
This study is aimed towards understanding the effect of perceived CSR initiatives (PCSRI) on brand loyalty, and consumer based brand equity (CBBE) in Indian sportswear market. This study was conducted on a group of respondents in Delhi NCR region. Different categories of sportswear brands were chosen for an adequate representation of market share, price and country of origin. The findings indicate that positive and direct relationships exist between PCSRI and consumer trust, PCSRI and brand loyalty; PCSRI and CBBE; consumer trust and brand loyalty; consumer trust and CBBE; brand loyalty and CBBE. The study contributes to the existing literature in understanding the role of PCSRI in building brand loyalty, consumer trust and CBBE. The study will help managers in implementing action plans for enhancing brand loyalty and CBBE in Indian sportswear industry.